Sur la conjonction du littéraire, du religieux et du savoir existentiel dans les Mémoires d’outre-tombe de Chateaubriand - Kamińska, Aleksandra (Studia Romanica Posnaniensia, 2015)
The aim of this paper is to present the relationship between literature, religion and existential knowledge in the memorial work of François-René de Chateaubriand. The first main problem is the transmission of universal values represented by Christianity. The second problem are narrator’s tragic experiences that become a source of precious knowledge communicated to the reader. These narrative stakes, reinforced by rhetorical persuasion, are crucial to ensure immortality of the author through the pertinence of his voice addressed to posterity.